Exploring the Impact of Music Education on the Psychological and Academic Outcomes of Students: Mediating Role of Self-Efficacy and Self-Esteem - Sun, Jian (Frontiers in Psychology, 2022)
In the recent years, there are a growing interest of scholars and practitioners to explore the factors which lead to improve the psychological well-being of students. Due to the tough challenges faced by the students during their academic life, severe issues of stress, anxiety and mental problems emerge which not only affect their students academic performance but also have a long-lasting impact on their future careers. The pandemic accelerates the stress level, anxiety and mental issues among the students. The main purpose of this study was to examine whether music education impacts on psychological well-being and academic performance of students. This study also investigates the mediating effect of self-esteem and self-efficacy. To the best of our knowledge, little to no study exists especially from an Asian country's perspective which explores the relationship of music education on psychological well-being and performance of students. This study was conducted in undergraduate and graduate institutions of China. This study was quantitative in nature and data were collected from 319 respondents. The structural equation modeling (SEM) technique was employed for data analysis. Results reveal that music education has a positive significant impact on psychological well-being which in turn improves the academic performance of students. Moreover, psychological well-being also has a significant and positive impact on the academic performance of students. Self-efficacy and self-esteem significantly mediate the relationship between music education and psychological well-being. Finding of this study explore new avenues for future research in the area of music education and psychological well-being. Result of this study suggest that the policymakers and practitioners should make such policies that encourage educational institutes to adopt music education to improve the psychological well-being of students.